Analisis Kohesi Dan Koherensi Berita Populer Surat Kabar Online Go.Riau.Com - Suriadiman, Noprieka; Anita, Fenny; Triana, Neni (JURNAL PENDIDIKAN ROKANIA, 2024)
Discourse is the highest form at the linguistic level. Discourse is formed from several paragraphs and drives the language functions contained therein. Good discourse is discourse that pays attention to the relationships between sentences so that coherence can be maintained. Therefore, consistency of meaning and cleanliness of the form of written discourse is one of the key factors that increases the readability factor. Good and complete discourse must be seen in terms of the cohesion and consistency of the discourse produced. This research aims to describe the use of cohesion and coherence in forming the integrity of the popular news discourse of the online newspaper go.riau.com. This study used descriptive qualitative method. The data source in this research is discourse in the popular online newspaper go.riau.com. The discourses chosen are 6 discourses and the research data is in the form of fragments of news discourse that contain cohesion and coherence. Research data was collected using documentation techniques. Based on the research results, there are markers of cohesion and coherence. Cohesion markers can be divided into two, namely grammatical cohesion and lexical cohesion. Grammatical cohesion markers were found in 41 research data and lexical cohesion markers were found in 22 data. Coherence markers in this research were found in 34 research data